Design and simulation of an adaptive beam smart antenna using MATLAB - Aaron Don M. Africa; Rica Rizabel M. Tagabuhin; Jan Jayson S. D. Tirados (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Signals transmitted over a long range of distance may pass through several obstacles and scatter, taking multiple paths to reach the receiver. Beamforming antennas are controlled electronically to adjust the radiation pattern following the first received signal. This allows the antenna to maximize the received signal and consequently, suppress the interfering signals received. A smart antenna should be able to diminish noise, increase the signal to noise ratio, and have better system competence. The adaptive beam makes use of the spacing of the several antennas and the phase of the signal of each antenna array to control the shape and direction of the signal beam. This paper focuses on the use of smart antennas using an adaptive beam method as a better system for the transmission of signals. A simulation between the existing Omnidirectional antenna system and the smart antenna system will be made and compared. The paper will discuss the corresponding advantages that a smart antenna system has compared to the Omnidirectional antenna system.